Organism- and Mortality-Specific Cardiorespiratory Patterns in Late-Onset Neonatal Sepsis: A Four-Neonatal Intensive Care Unit Study of Very Low Birth Weight Infants - Kausch, Sherry L.; Sullivan, Brynne A.; Sahni, Rakesh; Vesoulis, Zachary A.; Travers, Colm P.; Lake, Douglas E.; Fairchild, Karen D.; the Predictive Monitoring Consortium (American Journal of Perinatology, 2025)
Late-onset neonatal sepsis (LOS) in very low birth weight (VLBW) preterm infants varies in severity from mild to fatal and often presents with cardiorespiratory instability. We hypothesized that heart rate (HR) and systemic oxygenation (SpO2) patterns would differ based on pathogen type and mortality.We analyzed HR and SpO2 changes before LOS diagnosis for Gram-negative, Coagulase-negative Staphylococcus, and other Gram-positive bacteria (GN, CONS, OGP) and compared survivors and nonsurvivors. Using continuous every-2-second vital sign data from 365 VLBW infants in four neonatal intensive care units, we calculated nine HR and SpO2 metrics over a 96-hour window.GN LOS was associated with a slightly higher HR, more negative skewness of HR, and higher cross correlation of HR-SpO2. Mortality was highest in GN LOS (22.7 vs. 4.6% CONS, 8.8% OGP). Nonsurvivors had distinct HR and SpO2 patterns.These findings highlight critical cardiorespiratory differences at LOS diagnosis associated with mortality risk.
Keywords: neonate; sepsis; infant; very low birth weight; infant; newborn